Penyusunan Standar Operasional Prosedur (SOP) Produksi Katekin dan Tanin dari Gambir - Wedy Nasrul; Rudi Kurniawan Arief; Afdhil Arel (Jurnal Pengabdian UntukMu NegeRI, 2024)
Standard Operating Procedures (SOP) for production are documents that contain step-by-step instructions to guide workers on how to carry out repetitive production processes for a job to achieve production goals. Production SOP function to guide workers in the production process and maintain the quality of the products produced. The Sharia Producer Cooperative "Gambir Anam Koto Mandiri" which produces catechins and tannins does not yet have a production SOP. So it is important to prepare SOP for catechin production and gambier farming to help workers in the production process and maintain the quality of the products produced. The activity method is in the form of training and mentoring. The results of training activities show that cooperative administrators can prepare SOP for the production of catechins and tannins. The results of the assistance show that cooperative members can produce gambier catechin and tannin in accordance with the SOP. Activities produce catechin and tannin products which are produced to meet specified quality standards